2016
DOI: 10.2141/jpsa.0150131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graded Dietary L-arginine Supply on Organ Growth in Four Genetically Diverse Layer Lines during Rearing Period

Abstract: Little information has been available about the influence of genetic background and dietary L-arginine (Arg) supply on organ growth of chickens. Therefore, the present study examined the effects of a graded ad libitum Arg supply providing 70, 100 and 200% of recommended Arg concentration on organ growth of female chickens from hatch to 18 weeks of age. The chickens derived from four layer lines of different phylogeny (white vs. brown) and laying performance (high vs. low). Based on residual feed and absolute b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The growth and development of digestive organs directly affect the digestive and absorptive capacity of nutrients, and the weight and size of the digestive organs can be an indicator of physiological function. Although organ growth was equally directed within each organ group, the sensitivity to dietary arginine differed among organ groups as well as within them (Lieboldt et al 2015). Individual organ sensitivities might be mediated through the organ-specific expression of arginine uptake transporters, the cationic amino acid transporters (CAT) (Humphrey et al 2004;Humphrey and Klasing 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The growth and development of digestive organs directly affect the digestive and absorptive capacity of nutrients, and the weight and size of the digestive organs can be an indicator of physiological function. Although organ growth was equally directed within each organ group, the sensitivity to dietary arginine differed among organ groups as well as within them (Lieboldt et al 2015). Individual organ sensitivities might be mediated through the organ-specific expression of arginine uptake transporters, the cationic amino acid transporters (CAT) (Humphrey et al 2004;Humphrey and Klasing 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Arginine is one of the critical essential amino acids for poultry because, unlike mammals, they cannot synthesise arginine ( Birmani et al., 2019 ); however, arginine has received little consideration in layer hens. Arginine is required to enhance the performance and immunity in layers as it serves as a precursor of protein, creatine, proline, polyamines, and nitric oxide ( Lieboldt et al., 2015 ).…”
Section: Importance Of Dietary Amino Acids In Laying Hensmentioning
confidence: 99%
“…Increasing dietary arginine has improved feed intakes, but it has negative effects at levels of more than 12.7 g/kg ( Yuan et al., 2015 ) although arginine can act as appetite-stimulating factor in layer hens ( Lieboldt et al., 2015 ). In addition, arginine can stimulate the secretion of luteinizing hormone and positively impact follicle development and ovulations ( Youssef et al., 2015 ; Yuan et al., 2015 ).…”
Section: Importance Of Dietary Amino Acids In Laying Hensmentioning
confidence: 99%
“…Lelis et al suggested that increasing the digestible Valine in the diet can linearly enhance the feed intake of Jing Tint 6 chicks, justifying a moderate increase in Valine [ 48 ]. Arginine is a precursor to protein, creatine, Proline, polyamines, and nitric oxide, and it can help improve production performance and immunity in Jing Tint 6 chicks [ 49 ]; the model-predicted requirements for Arginine were slightly higher than the results from previous studies but remained within an acceptable range without causing adverse effects [ 50 ]. Isoleucine levels below 4.0 g/kg [ 51 ] and above 8.1 g/kg [ 52 ] were detrimental to Jing Tint 6 chicks’ feed intake, but the model predicted Isoleucine requirements to fall between these limits.…”
Section: Discussionmentioning
confidence: 99%